2018
DOI: 10.1111/ibi.12701
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Yellow‐legged Gulls increase consumption of terrestrial prey after landfill closure

Abstract: The ecology of opportunistic foragers can be highly dependent on anthropogenic food sources, such as landfills, resulting in changes in several ecological and demographic aspects. The total closure of several landfill sites and the use of deterrence systems to prevent access to the remaining open landfill sites in a region in the northern Iberian Peninsula provided an excellent opportunity to evaluate the consequences of landfills on the trophic ecology of an opportunistic forager, the Yellow‐legged Gull Larus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…They were ringed (in order to avoid pseudo‐replications in possible subsequent visits to the colonies where we were not able to take all the samples in 1 day), and 4‐6 mantle feathers were taken from each chick for the stable isotope analysis ( δ 15 N and δ 13 C). Previous studies carried out in three of these colonies reported no differences between adults' and chicks' diet in the breeding period (Zorrozua et al , ), suggesting that the diet of the chicks may be also used to infer adults' foraging ecology.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…They were ringed (in order to avoid pseudo‐replications in possible subsequent visits to the colonies where we were not able to take all the samples in 1 day), and 4‐6 mantle feathers were taken from each chick for the stable isotope analysis ( δ 15 N and δ 13 C). Previous studies carried out in three of these colonies reported no differences between adults' and chicks' diet in the breeding period (Zorrozua et al , ), suggesting that the diet of the chicks may be also used to infer adults' foraging ecology.…”
Section: Methodsmentioning
confidence: 92%
“…The recent closure of several landfills within the region has resulted in a decrease in the consumption of landfill prey, which has been found to be replaced in the breeding season by an increase in consumption of prey of terrestrial origin, but not of marine origin (Zorrozua et al , ). Our results suggest that harbours may not be suitable as a main alternative source of food for those colonies situated at a considerable distance from them, while at the same time, they are compatible with an increasing exploitation of terrestrial habitats during the summer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reduction in the number of landfills or measures to impede access by wildlife to these facilities; Landfill Directive 1999) conducted during the last few decades in the metropolitan area of Barcelona have likely reduced the accessibility of this human-related subsidiary resource to the yellow-legged gull. This situation could force that gulls consume more terrestrial prey items (Zorrozua et al 2020) that acquire relatively easy in the urban areas predating on urban birds. In fact, we could not rule out the possibility that some of the organic resources of human origin or mammals may be obtained inside the city in the urban parks or touristic beach areas (Navarro et al 2016;Schwartz et al 2018).…”
Section: Discussionmentioning
confidence: 99%